2019
DOI: 10.1108/aam-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary impact – the arts join informal STEM programs

Abstract: Purpose Middle school participants in the USA attending an on-campus university informal science program indicate an increase in interest toward careers and disciplines in STEM or STEAM (science, technology, engineering and mathematics and the arts). Parents or guardians confirm the change. The paper aims to discuss this issue. Design/methodology/approach Participants attended “inquiry-based” lectures by scientists and “hands-on” activities conducted by volunteers on campus at a public university over four m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Intention is comprised primarily of three inputs, informal STEM programs (e.g., attitude toward the behavior), subjective norms, and perceived control and self-efficacy. TRA can be applied to the fields of social psychology (with applications in marketing), science education, the arts, and sociology (Tretola et al, 2019). Figure 3 shows the Theory of Reasoned Action (TRA).…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Intention is comprised primarily of three inputs, informal STEM programs (e.g., attitude toward the behavior), subjective norms, and perceived control and self-efficacy. TRA can be applied to the fields of social psychology (with applications in marketing), science education, the arts, and sociology (Tretola et al, 2019). Figure 3 shows the Theory of Reasoned Action (TRA).…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 99%
“…Figure 3 shows the Theory of Reasoned Action (TRA). Tretola et al (2019) applied the TRA to construct a conceptual framework for the study examining the impact of a university STEM program along with -hands-on‖ activities that include the arts. For each STEM topic, the results showed that interest grew noticeably for students who had expressed low interest in the initial pre-lecture survey using paired samples t-tests.…”
Section: Theory Of Reasoned Action (Tra)mentioning
confidence: 99%